PENGARUH PSYCHOLOGICAL EMPOWERMENT TERHADAP WORK-FAMILY ENRICHMENT DENGAN AFFECTIVE COMMITMENT SEBAGAI VARIABEL MEDIASI - Gustina DR; Adi Rahmat; Agus Seswandi (Indragiri Research Center (ingreat), 2025)
Work-family enrichment is an important point to pay attention to because employees in the government sector often face high work demands and irregular schedules. Increasing work-family enrichment can help improve employee welfare and overall government organizational performance. The aim of this research is to determine the effect of Psychological Empowerment on Work-family enrichment through Affective Commitment as a mediating variable. This research is a type of quantitative research with a causality research design and the population is all State Civil Apparatus in Indragiri Hilir Regency. with a sample of 150 people. Data collection techniques using questionnaires and distribution using Google Form. The data analysis tool in this research is Structural Equation Modeling (SEM) processed using SmartPLS 3.2.9 for data processing. The results of this research are that Psychological Empowerment has a significant direct influence on Work-Family Enrichment and an indirect influence, namely through the mediation of Affective Commitment.